Dynamic responses to smoking bans: Evidence from young adults in a developing country - Camila Steffens; Paula Carvalho Pereda (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
Smoking bans have been widely implemented, despite mixed evidence on their effectiveness in reducing firsthand smoking. This paper provides novel insights into the dynamic impacts of smoking bans in the context of a large developing country, Brazil, that had more than 18.6 million regular smokers in 2013. Our estimation strategy exploits the staggered implementation of comprehensive smoking bans in Brazilian state capitals using an event-study framework. We also leverage the variation in policy enforcement across cities. Our results indicate that bans reduced smoking prevalence by up to 15% among young adults, particularly when rigorously enforced. This effect is primarily driven by smoking cessation, while the impact on initiation is relatively modest. Our analysis suggests that the Brazilian policy prevented roughly USD 53 million in costs in the capitals where it was highly enforced.
Keywords: D04; D12; I12; I18; 330; Smoking bans; Addiction; Policy enforcement; Difference-in-differences; Development